Hybrid collapse confirms the specific status of triatoma bahiensis sherlock and serafim, 1967 (hemiptera, triatominae), an endemic species in Brazil - Alevi, Kaio Cesar Chaboli [UNESP]; Pinotti, Heloisa [UNESP]; De Araújo, Renato Freitas; De Azeredo Oliveira, Maria Tercilia Vilela [UNESP]; Da Rosa, João Aristeu [UNESP]; Mendonça, Vagner Jose (American Society of Tropical Medicine and Hygiene, 2018)
Six to seven million people worldwide are estimated to be infected with Trypanosoma cruzi, the etiologic agent of Chagas disease transmitted mainly by triatomines. Triatoma bahiensis was recently collected in the Brazilian state of Bahia and revalidated using different approaches. The main criterion used to define a 'good' biological species is reproductive isolation, so we evaluated the cytogenetics of first-generation (F1) hybrids resulting from the experimental cross between T. bahiensis females and Triatoma lenti males to possibly characterize the postzygotic isolation associated with the hybrid breakdown. All cells analyzed presented a karyotype of 2n = 22 and a pair of univalent autosomes. This chromosome behavior represents hybrid collapse and underscores the specific status of T. bahiensis. Thus, we have characterized the presence of the hybrid collapse phenomenon in an experimental cross, and we confirm the specific status of T. bahiensis, thus contributing to the Triatominae taxonomy.